2002
DOI: 10.1093/occmed/52.6.311
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide sprayers' knowledge, attitude and practice of pesticide use on agricultural farms of Ethiopia

Abstract: Pesticide sprayers from five state-owned agricultural farms took part in a study that evaluated their knowledge, attitude and practice of pesticide use on farms. Demographic features of the sprayers showed that the majority of them had primary-level education. The duration of work as sprayers on the farms ranged from 1 month to approximately 10 years, with 59% of them having worked as sprayers for <5 years. Their knowledge about hazards from pesticides was indicated by the responses they gave to the standard q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
109
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 20 publications
15
109
2
Order By: Relevance
“…Lack of protective equipment use has been reported among farmers of many countries, for example, Australia (MacFarlane et al, 2008), Brazil (Recena et al, 2006), Sri Lanka (Sivayoganathan et al, 1995), Egypt (Stewart, 1996), Gaza strip (Yassin et al, 2002), Ethiopia (Mekonnen and Agonafir, 2002) and United Arab Emirates (Gomes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of protective equipment use has been reported among farmers of many countries, for example, Australia (MacFarlane et al, 2008), Brazil (Recena et al, 2006), Sri Lanka (Sivayoganathan et al, 1995), Egypt (Stewart, 1996), Gaza strip (Yassin et al, 2002), Ethiopia (Mekonnen and Agonafir, 2002) and United Arab Emirates (Gomes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These include characteristics of individual farmers such as their gender [42], education level [19], farming years [43], planting size [44], other economic features such as portion of household income generating from farming [45], government and policy factors such as the participation in pesticide use training organized by governments [46]; knowledge about types of prohibited pesticides [47], views towards frequent and massive use of pesticides on generating pesticide residue [29], view towards massive use of pesticides which in turn damage the surrounding environment [48]. In addition, we have included a new variable, which is farmer's knowledge on the "Guideline for safety application of pesticides".…”
Section: Resultsmentioning
confidence: 99%
“…Other parts of sub-Saharan Africa have similar problems with the widespread use of highly toxic and illegal pesticides (Ecobichon 2001;Williamson et al 2008;Handford et al 2015). Like in many African countries, also in Ethiopia, different studies conducted on knowledge, attitude and perception (KAP) among smallholders (Mekonnen and Agonafir 2002;Amera and Abate 2008;Mengistie et al 2014;Damte and Tabor 2015) have shown that farmers have low knowledge, attitude and perception on pesticides use. Other interesting studies done in sub-Saharan Africa (Gogo et al 2014;Faustin et al 2015;Simon et al 2014) can be seen as an attempt to combine some elements of the system of provision into an integrated strategy, emphasizing the need to provide low or nontoxic insecticides (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies conducted on knowledge, attitude and behaviour among smallholders (Mekonnen and Agonafir 2002;Obopile et al 2008;Macharia et al 2013;Abang et al 2014;Damte and Tabor 2015) have shown that unsafe use of pesticides is common in developing countries including in Ethiopia. However, little research has explored farmers' actual practices, while applying an approach based on practice theory could improve our understanding of these practices and the changes therein.…”
Section: Introductionmentioning
confidence: 99%